Fatigue crack closure: A myth or a misconception?. Issue 12 (29th July 2019) - Tong, Jie; Alshammrei, Shaher; Lin, Bing; Wigger, Tim; Marrow, Thomas
Abstract: In this paper, we have extended our previous study on fatigue crack closure to examine the phenomenon of crack opening displacement (COD) and its impact on the crack tip fields in both 2D and 3D specimen geometries using full‐field experimental measurements and integrated finite element modelling. Digital image correlation (DIC) and digital volume correlation (DVC) were used to measure the near‐tip material responses on the surfaces (DIC) and the interior (DVC) of the specimens. Materials with elastic‐plastic and large plastic characteristics were chosen for the study, where plasticity‐induced premature contact between the crack flanks is known to occur. Displacement maps around the cracks were obtained using DIC and DVC at selected load increments and were introduced as boundary conditions into the finite element (FE) models to obtain the "effective" crack driving force in terms of J‐integral, and the results were compared with those "nominal" from the standard FE analysis. Both visual observation and compliance curves were used to determine the "crack opening" levels; whilst the impacts of the crack opening on the crack driving force J and the normal strains ahead of the crack tip were evaluated in 2D and 3D. The results from the study indicate that, crack closure, although clearly identifiable in the compliance curves, does not appear to impact on global crack driving force, such as J‐integral, or strains ahead of the crack tip; hence, it may well be a misconception.